Big Broadcast - Cayado, Tony (Sampaguita Pictures, 2005)
Two star struck teenagers risk the ire of their strict and abusive aunt when they decide to watch their idols in the Big Broadcast. Sisters Angge and Susan cannot believe their luck when they are handpicked by the day's hearthrobs, Eddie Gutierrez and Jose Mari to become their new on-screen partners. Getting into all sorts of trouble and resorting to mischief in pursuit of their dreams of becoming artistas, they are chased by the police, get into fistfights, and are even held captive by their very own aunt and cousins, who are artista-wannabes themselves! All these happen inside a movie studio, amidst a flurry of color and theatrical settings that have Egyptian, Las Vegas, and even Caribbean themes.